Potenciais turísticos naturais e culturais de Arraias/TO: levantamento, formas e processos do patrimônio local - Ribeiro, Aline Alves (Universidade Federal do Tocantins, 2021)
The present research sought to carry out a survey of the natural and cultural tourist potentials of Arraias-TO, considering the forms and processes of the local heritage, represented through the investigated potentialities. The general objective of the research was to carry out a survey with the materialization of a map of the natural and cultural tourist potentials of the municipality of Arraias-TO, identifying them in their forms and processes, in order to carry out an identification and classification of the possibilities of activities to be carried out. be made at the points found. The methodology applied to the research considered participant observation with technical instruments of academic consultancy; planning and execution of the survey; field work aligned with the research; monitoring the results achieved; survey of data in the field and registration of information. The research resulted in the creation of a Matrix of Tourist Potentials existing in the territory of Arraias that presents the tourist points of the city and their characteristics with the possibilities of use for tourism, in addition to the creation of the Map of Tourist Potentials of Arraias with specialized information.